Protective Effect of D-Methionine on Body Weight Loss, Anorexia, and Nephrotoxicity in Cisplatin-Induced Chronic Toxicity in Rats. (September 2018) - Lin, Ming-Tai; Ko, Jiunn-Liang; Liu, Te-Chung; Chao, Pei-Tsen; Ou, Chu-Chyn
D-methionine is a sulfur-containing amino acid that can act as a potent antioxidant. Anorexia and nephrotoxicity are side effects of cisplatin. The protective effects of D-methionine on cisplatin-induced anorexia and renal injury were investigated. The model of chronic cisplatin administration (5 mg/kg body weight) involved intraperitoneal injection on days 1, 8, and 15 and oral D-methionine (300 mg/kg body weight) coadministration daily for 20 days. On the 21st day of treatment, food intake and body weight in the cisplatin-treated group significantly decreased by 52% and 31%, respectively, when compared with a control group. D-methionine coadministration with cisplatin decreased food intake and body weight by 29% and 8%, respectively. In cisplatin-treated rats, white blood cell, mean corpuscular volume, and platelet values significantly decreased, while mean corpuscular hemoglobin concentration significantly increased by 8.6% when compared with control rats. Cisplatin administration resulted in significantly decreased feeding efficiency, elevated renal oxidative stress, and reduced antioxidative activity. Leukocyte infiltration, tubule vacuolization, tubular expansion, and swelling were observed in the kidneys of cisplatin-treated rats. Oral D-methionine exhibited an antianorexic effect, with improvement in food intake, feeding efficiency, and hematological toxicities, as well as a protective effect against nephrotoxicity by elevated antioxidative activity. D-methionine may serve as a chemoprotectant in patients receiving cisplatin as part of a chemotherapy regimen.